Lumped Element Bandpass Micromachined Filter Design for DCS1800(GSM) - Muller, A.A.; Neculoiu, D.; Takacs, A.; Vasilache, D.; Cismaru, A.; Giacomozzi, F. (MELECON 2006 - 2006 IEEE Mediterranean Electrotechnical Conference, 2006)
The paper presents the design and electromagnetic simulation of new lumped elements bandpass filter for DCS1800 (GSM) applications. The filter structure is based on membrane supported spiral inductors and bulk silicon supported interdigitated capacitors. By using micromachining technologies the quality factor of the spiral inductor increases so that the bandpass insertion losses of the filter are improved